2016
DOI: 10.1128/jvi.00451-16
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alpha Subtype-Specific Suppression of HIV-1 InfectionIn Vivo

Abstract: Although all 12 subtypes of human interferon alpha (IFN-␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(204 citation statements)
references
References 85 publications
(120 reference statements)
9
188
5
Order By: Relevance
“…These results indicate that additional factors, possibly including IFNα2 and/or other IFN subtypes, shape the transmitted founder phenotype. Because there are a total of 13 IFNα subtypes as well as other type 1 IFNs such as IFNω, some of which inhibit HIV-1 even more potently in vitro and in animal models (79)(80)(81), it will be critical to evaluate to what extent they contribute alone, or in combination, to the HIV-1 transmission bottleneck. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that additional factors, possibly including IFNα2 and/or other IFN subtypes, shape the transmitted founder phenotype. Because there are a total of 13 IFNα subtypes as well as other type 1 IFNs such as IFNω, some of which inhibit HIV-1 even more potently in vitro and in animal models (79)(80)(81), it will be critical to evaluate to what extent they contribute alone, or in combination, to the HIV-1 transmission bottleneck. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IFN-Is can suppress HIV-1 replication in vitro (3). IFN-Is have also been shown to inhibit initial simian immunodeficiency virus (SIV) infection in rhesus macaques (7) and HIV-1 infection in humanized mice (8,9) in vivo. Furthermore, reports also indicated that transmitted/founder viruses isolated from patients are less sensitive to suppression by IFN-α in cultured cells than their corresponding viruses present during chronic infection, suggesting that resistance to IFN-Imediated inhibition may provide a selective advantage during transmission and initial infection (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that IFN-I can suppress HIV-1 replication in vitro (5), and the major anti-HIV-1 restriction factors are encoded by ISGs (5). In addition, IFN-I has been shown to inhibit early HIV-1 infection in humanized mice (hu-mice) (9) and SIV infection in rhesus macaques in vivo (10). These observations suggest that a robust IFN-I response helps to control or limit initial HIV-1 and SIV infection.…”
Section: Introductionmentioning
confidence: 99%